Detection of hepatitis D virus RNA carrying large fragment deletions in patients with severe hepatitis B/D receiving oral antiviral therapy. Issue 4 (21st January 2015) - Hsu, Chao‐Wei; Chao, Mei; Chen, Yi‐Cheng; Chang, Ming‐Ling; Huang, Shiu‐Feng; Yeh, Chau‐Ting
<x xml:space="preserve">Abstract</x> A chronic lymphocytic leukemia patient had achieved complete virological suppression of hepatitis B virus (HBV) by oral antiviral therapy. Unexpectedly, fulminant hepatitis D virus (HDV) reactivation occurred, resulting in mortality. Cloning and sequence analysis identified a novel large fragment HDV deletion mutant containing only 69% of the standard genome. Reverse transcription‐PCR assay revealed persistence of this mutant with variations of the wild‐type‐to‐mutant ratios during the clinical course. Serum samples from 405 patients with chronic hepatitis B were then submitted for HDV RNA analysis. Of them, 20 (4.9%) were positive for HDV RNA and 5 HDV RNA large fragment deletions were identified in three patients, all under entecavir treatment. Two of them suffered from acute hepatitis exacerbations leading to liver failure while the third had repeated hepatitis flares. The peak bilirubin levels in these three patients were significantly higher than the others without large fragment deletions (P = 0.003). The deleted regions (527–702 bases) encompassed two ribozyme domains as well as part of the hepatitis D antigen (HDAg) reading frame. In conclusion, exacerbations of hepatitis D could occur, leading to fulminant hepatitis, even after complete virological suppression of HBV. Large fragment HDV RNA deletions were identified in some hepatitis D patients who were treated with entecavir but still experiencing severe hepatitis. J. Med. Virol. 87:634–641, 2015. © 2015 Wiley Periodicals, Inc.